3D cloud and storm reconstruction from satellite image - Somporn Chuai-Aree; Jäger, Willi; Bock, Hans Georg; Krömker, Susanne (Modeling, simulation and optimization of complex processes, 2008)
The satellite images in Asia are produced every hour by Kochi University, Japan (URL http://weather.is.kochi-u.ac.jp/SE/00Latest.jpg). They show the development of cloud or storm movement. The sequence of satellite images can be combined to show animation easily but it is shown only from the top-view. In this paper, we propose a method to condition the 2D satellite images to be viewed from any perspective angle. The cloud or storm regions are analyzed, segmented and reconstructed to 3D cloud or storm based on the gray intensity of cloud properties. The result from reconstruction can be used for a warning system in the risky area. Typhoon Damrey (September 25 - 27, 2005) and typhoon Kaitak (October 29 - November 1, 2005) are shown as a case study of this paper. Other satellite images can be conditioned by using this approach as well.
Gesehen am 17.08.2018